2021
DOI: 10.1136/rapm-2020-102417
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral mandibular block improves pain relief and morphine consumption in mandibular osteotomies: a prospective, randomized, double-blind, placebo-controlled clinical trial

Abstract: BackgroundThe sensory innervation of the lower jaw mainly depends on the third root of the trigeminal nerve, the mandibular nerve (V3). The aim of this single-center, prospective, randomized, double-blind, placebo-controlled study was to evaluate the effectiveness of bilateral V3 block for postoperative analgesia management in mandibular osteotomies.Methods107 patients undergoing mandibular surgery (75 scheduled osteotomies and 32 mandible fractures) were randomized in two groups. A bilateral V3 block was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For patients undergoing bimaxillary surgery, ultrasound-guided trigeminal nerve block with 0.25% ropivacaine was effective in reducing intraoperative sufentanil and remifentanil consumption and decreasing the incidence of POV (20% vs. 40%, P = 0.028) [ 14 ]. A study by Bertuit et al [ 15 ] examined the role of bilateral mandibular block with 0.75% ropivacaine. Their results suggested that bilateral mandibular block effectively decreased morphine consumption but resulted in more incidence of PONV (46.0% vs. 21.1%, P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients undergoing bimaxillary surgery, ultrasound-guided trigeminal nerve block with 0.25% ropivacaine was effective in reducing intraoperative sufentanil and remifentanil consumption and decreasing the incidence of POV (20% vs. 40%, P = 0.028) [ 14 ]. A study by Bertuit et al [ 15 ] examined the role of bilateral mandibular block with 0.75% ropivacaine. Their results suggested that bilateral mandibular block effectively decreased morphine consumption but resulted in more incidence of PONV (46.0% vs. 21.1%, P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…In this review, most studies revealed significantly lower incidences of PONV when combined nerve block with general anesthesia. However, Bertuit et al [ 15 ] reported conflicting findings. They found bilateral mandibular block was associated with a higher incidence of PONV, although postoperative morphine consumption was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Such results have already been described in a recent study evaluating the effectiveness of an ultrasound-guided mandibular nerve block. 16 Moreover, it has been demonstrated that PONV after orthognathic surgery is the result of a multiple factors interaction including age, gender, pain intensity, surgical duration, use of halogens, consumption of opioids…but is not correlated with anesthetic's experience. 30 Further studies are necessary to better understand the risk factor of PONV in double-jaw surgery.…”
Section: Original Researchmentioning
confidence: 99%
“…Prospective randomized clinical trials [9,10], retrospective cohort study [11,12], and metaanalysis [13,14] have reported that application of MMA is associated with improved pain control and less opioid consumption. However, although the benefit of MMA is obvious, adherence to MMA is not reported clearly, which determines the actual outcomes of surgical patients [4,15].…”
Section: Introductionmentioning
confidence: 99%